Quantity and quality of written feedback action plans and student reflections before and after the introduction of a modified miniCEX assessment form - R Djajadi; M Claramita; G Rahayu (South African Medical Association, 2017)
Background. Mini-clinical-evaluation exercise (mini-CEX) assessment forms that have been modified with the addition of specific spaces on separate sheets are expected to improve the quantity and quality of written feedback and the action plan for further learning which is agreed upon, and to encourage written reflection.Objective. To test whether the modified mini-CEX assessment forms improve the quantity and quality of the written feedback, action plan and student reflection in the mini-CEX assessment process.Methods. Data collection was conducted over 3 months. Data analysis used the c2 test to compare the quantity and quality of written feedback, action plans, and reflections before and after the introduction of a modified mini-CEX assessment form.Results. Twenty-four clinical teachers and 44 clinical students participated in this study. The percentage of written feedback increased by 39%, and the specificity increased by 30.1% (p=0.001). The percentage of written action plans increased by 37%, and the specificity increased by 17.7% (p=0.001). The percentage of written reflection in the new spaces on the modified forms reached 73%, and 49.2% were classified as ‘specific’.Conclusion. The use of modified mini-CEX assessment forms, with the addition of extra spaces on separate sheets, improved the quantity and quality of written feedback and action plans, and encouraged written reflection.